Federal Reserve Monetary Policy, 1922-33: A Reinterpretation - Wicker, Elmus R. (Journal of Political Economy, 1965)
But I beg of you not to despise monetary history; for I am sure that the monetary policy of nations is often unintelligible without some understanding of the queer institutional jungles out of which it has sprung.